Literature Review of Concepts, Applications, and Challenges in Subsea Pipeline Risk and Reliability Management - Nyein Zin Latt (Collaborate Engineering Daily Book Series, 2023)
Subsea pipelines are one of the important infrastructures in the oil and gas industry, which function to connect production wells at sea with processing facilities on land. Subsea pipelines have complex challenges and risks, such as environmental, operational, technical, and economic factors, which can affect the performance and reliability of subsea pipelines. Therefore, effective and efficient risk and reliability management of subsea pipelines is needed, which can identify, analyze, evaluate, and control risks, as well as improve the quality and life of subsea pipelines. This article aims to review the literature on concepts, applications, and challenges in risk management and reliability of subsea pipelines. The method used is literature study, by collecting, grouping, and summarizing information from various primary sources, such as scientific journals, books, and standards. The results and discussion show that there are various methods, models, techniques, and tools used in risk and reliability management of submarine pipelines, such as Bayesian Network, DNV RP F107, integrity management system, inspection, maintenance, and repair. This article also discusses the advantages, disadvantages, and challenges of each method, model, technique, and tool, as well as provides recommendations and suggestions for further research. It is hoped that this article can contribute to researchers, practitioners, and policymakers in the field of risk management and reliability of submarine pipelines.